Managing Complementary Assets to Build Cross-Functional Ambidexterity: The Transformation of Huawei Mobile. (December 2021) - Yan, Mengling; Hu, Yanni; Dong, Xiaoying
ABSTRACT: During technology transitions, incumbents are frequently faced with the ambidextrous challenge of exploiting existing capabilities and exploring new ones. While extant studies focus on radical changes in the product domain, we notice radical changes can happen in both product and market domains. Pioneering studies indicate that cross-functional ambidexterity addresses this challenge at the business-unit level by juxtaposing exploration and exploitation across different functional domains (particularly in product and market domains) and that complementary assets address this challenge at the organizational level. However, how efforts at two levels can be combined to build cross-functional ambidexterity and what roles complementary assets play remain unclear. Therefore, this study conducts an in-depth case study of Huawei Mobile, which managed to achieve superior performance during a technology transition that triggers radical changes in both product and market domains. We find that multi-level synergies contribute to the transition process. Specifically, cross-functional ambidexterity is constructed by prioritizing exploration in the product domain ahead of that in the market domain, and that it generates learning, brand and channel extension, matching, and brand alliance benefits at the business-unit level. Complementary assets help to reduce the uncertainty of exploration and resolve functional conflicts at the organizational level. 摘要: 在技术转型过程中，在任企业往往面临利用已有能力和探索新能力的双元困境。已有研究所讨论的激进式技术转型主要发生在产品领域，而我们的研究则关注在产品和市场领域同时发生激进式变革的技术转型。早期研究提出，在业务单元层构建的跨职能双元能力和在组织层构建的互补性资产，能够共同推进不同职能领域的探索和利用活动。但这两个层面的组织努力如何结合起来构建组织层的跨边界双元能力以及互补性资产在其中发挥何种作用尚不清楚。为此，本文针对华为手机业务进行深度案例研究，因为该业务历经产品和技术领域的激进式变革却仍然取得卓越绩效。我们发现多层次的协同促成了其转型过程。具体而言，跨职能双元能力得益于在产品领域优先进行探索活动，在业务单元层形成学习效应、品牌渠道扩展、匹配效应和品牌联盟效应。互补性资产则在组织层面发挥降低探索活动不确定性和缓解部门冲突的作用。 АННОТАЦИЯ: В процессе технологических преобразований должностные лица часто сталкиваются с неоднозначной задачей, а именно использовать имеющийся потенциал и одновременно искать новые возможности. В то время как существующие исследования сосредоточены на радикальных изменениях в области производства, мы отмечаем, что радикальные изменения могут произойти как в области производства, так и в сфере рыночных отношений. Новейшие исследования показывают, что межфункциональная амбидекстрия решает эту проблему на уровне организационных подразделений, сопоставляя изучение и освоение в различных функциональных областях (особенно в сфере производства и рыночных отношений), и что дополнительные активы решают эту проблему на уровне организации. Однако остается неясным, как можно объединить усилия на двух уровнях для создания межфункциональной амбидекстрии и какую роль играют дополнительные активы. Таким образом, в данном исследовании проводится углубленное изучение ситуации в компании Huawei Mobile, которой удалось достичь превосходной производительности во время технологического перехода, который вызывает радикальные изменения как в области производства, так и в сфере рыночных отношений. Мы считаем, что многоуровневый синергизм способствует процессу технологического перехода. В частности, межфункциональная амбидекстрия строится на том, что процессу изучения в области производства придается большее значение, чем в рыночной сфере, и это способствует приобретению знаний, укреплению бренда и расширению рыночных каналов, обеспечению соответствия, а также развитию преимуществ альянса брендов на уровне организационного подразделения. Дополнительные активы помогают снизить неопределенность в процессе изучения и разрешить функциональные конфликты на уровне организации. RESUMEN: Durante las transiciones tecnológicas, los titulares se enfrentan con frecuencia al reto ambidiestro de explotar las capacidades existentes y explorar otras nuevas. Mientras que los estudios existentes se centran en los cambios radicales en la esfera del producto, observamos que los cambios radicales pueden producirse tanto en la esfera del producto como en la del mercado. Los estudios pioneros indican que la ambidestreza interfuncional aborda este reto a nivel de la unidad de negocio yuxtaponiendo la exploración y la explotación a través de diferentes esferas funcionales (especialmente en las esferas de producto y de mercado) y que los activos complementarios abordan este reto a nivel organizacional. Sin embargo, si no siendo claro cómo pueden combinarse los esfuerzos en ambos niveles para crear ambidestreza interfuncional o qué papel desempeñan los activos complementarios. Por consiguiente, este estudio lleva a cabo un estudio de caso en profundidad sobre Huawei Mobile, que logró alcanzar un desempeño superior durante una transición tecnológica que desencadena cambios radicales tanto en la espera del producto como en el mercado. Encontramos que las sinergias a varios niveles contribuyen al proceso de transición. En concreto, la ambidestreza interfuncional se construye dando prioridad a la exploración en la esfera del producto antes que en la del mercado, y que genera beneficios de aprendizaje, extensión de la marca y del canal, alineamiento y alianza de marcas a nivel de unidad de negocio. Los activos complementarios ayudan a reducir la incertidumbre de la exploración y a resolver los conflictos funcionales a nivel organizacional.